Perancangan Lean Manufacturing dengan Menggunakan Waste Assessment Model (WAM) dan VALSAT untuk Meminimumkan Waste (Studi Kasus: PT. XYZ) - Satria, Tamzil (Jurnal Rekayasa Sistem Industri, 2018)
As an industrial company, XYZ Ltd. engaged in beverages should pay attention to the detailed processes of each line of its production. This aims to minimize potential problems which may occur that can cause losses. This research aimed to minimize waste on the production floor by designing  lean manufacturing. Lean manufacturing is an approach that tries to eliminate waste that occurs in the value stream. The method used is Waste Assessment Model (WAM) that functions to identify waste in tea  production, and Value Stream Analysis Tools (VALSAT) which functions to select mappingtools used, based on WAM result. From the research result, it was found out  that the production time of original tea 450 ml took 20,255.4 seconds and the total lead time of product fulfillment for delivery to customers took 13.23 days. The average reject product was 0.65%, exceeding the company maximum standard. Based on the mapping, recommendation for improvement was  given to minimize waste, among others the elimination of Non Value Added (NVA) activity, the application of forecasting, and preventive maintenance activities. This research resulted in the waste identification, which  the biggest waste in this company was defect, decreasing the lead time of production time to become 14,767,4 second faster and Process Cycle Efficiency (PCE) which was increased from 39,12% to 53,66%.